Penerapan Prinsip Filsafat Progresivisme dalam Pembelajaran Kolaboratif PAI di SMP - Ricky Yoseptry; Rina Supriati; Iis Kurniawati; Heri Hasanudin (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Twenty-first-century education demands a paradigm shift from conventional, teacher-centered learning to student-centered learning. This demand aligns with the Kurikulum Merdeka, which emphasizes critical, creative, and collaborative competencies. The philosophy of progressivism (John Dewey) offers a theoretical foundation through the principles of learning by doing and cooperative learning. This study aims to gain an in-depth understanding of the implementation of progressivist principles in collaborative learning in Islamic Religious Education (PAI) at SMP Negeri 6 Darangdan. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation analysis. The findings indicate that the implementation of progressivism remains administrative rather than philosophical in nature. There is a significant gap between planning documents (lesson plans/teaching modules) that include progressive labels such as Problem-Based Learning and actual classroom practices, in which teachers’ roles as facilitators have not been optimally realized. Furthermore, although school managerial support is strong at the policy level, weaknesses were identified in the area of instructional leadership, as supervision focuses primarily on administrative completeness rather than on pedagogical coaching for teachers. This study concludes that progressive PAI learning requires strong integration between teachers’ pedagogical commitment and capacity-based managerial support.